1965
DOI: 10.1002/pol.1965.100031001
|View full text |Cite
|
Sign up to set email alerts
|

A unified approach to failure and its application to highly filled polymers

Abstract: Two interrelated general approaches to the study of structural failure of highly filled polymeric materials, e.g., a solid propellant, are described. These consist of the macroscopic (thermodynamics and continuum mechanics) and microscopic (molecular model) methods of analysis in conjunction with solid propellant experimental data. The thermodynamic investigation indicates that propellant material under loading goes through stages of stable and unstable behavior which depend upon the rate at which work is abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1965
1965
1965
1965

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…Crack velocities predicted by Equation (8) are of the order of 1.0 to 2.5 inches per minute, depending on crack length and test temperature, in excellent agreenment with the experimental observations.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Crack velocities predicted by Equation (8) are of the order of 1.0 to 2.5 inches per minute, depending on crack length and test temperature, in excellent agreenment with the experimental observations.…”
Section: Discussionsupporting
confidence: 63%
“…9 ) if the outer supports are restrained from lateral motion. Specifically, it was found that the normal stress a y across the shear is proportional to the applied shear stress T. and is, approximately, ry t 0.3o (8) where 'to is the shear force divided by the total area.…”
Section: Strip Biaxial Tensionmentioning
confidence: 99%